Medical treatment of lower urinary tract symptoms/benign prostatic hyperplasia: anything new in 2015. Issue 1 (January 2015) - Schauer, Ingrid; Madersbacher, Stephan
Abstract : Purpose of review: The purpose of this study is to provide an update on recent developments regarding the medical management of male lower urinary tract symptoms (LUTS). Recent findings: Silodosin improves storage/voiding symptoms and nocturia and is effective within the framework of a trial without a catheter. 5α-reductase inhibitors (5ARIs) are not associated with male breast cancer development. Alcohol consumption seems to increase the risk of high-grade prostate cancer under 5ARIs. The combination of α-blocker and 5ARIs remains a well established concept for benign prostatic hyperplasia/LUTS patients with an enhanced risk of disease progression. Tadalafil 5 mg/day monotherapy is a valid option particularly for men with LUTS and erectile dysfunction; the combination of Tadalafil 5 mg/day with a 5ARI is an interesting approach. The fixed-dose combination of α-blocker and antimuscarinic provides advantages regarding storage symptom improvement. This approach is currently primarily recommended as an add-on strategy. Mirabegron opens new horizons in the management of male LUTS and has no negative (but also no positive) urodynamic effects. Several encouraging novel approaches are currently in the experimental phase and might enhance our therapeutic armamentarium in the near future. Summary: The recent literature refines our knowledge on current therapeutic options and provides further evidence for an individualized, risk-adapted approach for male LUTS mainly depending on symptoms status, comorbidities (i.e. erectile dysfunction) and risk of disease progression.